Pemodelan Angkutan Sedimen Dan Perubahan Dasar Sungai (Studi Kasus: Sungai Juana) - Archyuda Farchan (Departement of Mathematics Education, 2024)
One of the causes of flooding that often occurs in the Pati Regency area is due to the reduced drainage capacity of the Juana River due to sedimentation. Sedimentation occurs due to many factors, including the slope of the land and bottom of the channel, river flow speed, sediment transport, and chemical reactions such as flocculation. Several software have been developed to calculate sediment transport rates and simulate aggradation/degradation in rivers, one of which is HEC-RAS. The results of the sediment transport simulation with HEC-RAS at the study location on the Juana River STA-37+613-STA 51+157 show that sedimentation occurred in the riverbed with a total of 146,000 m3 of sediment from 2019-2022 or 36,500 m3/year. The simulation results show a similar trend, namely that sedimentation occurs at the bottom of the channel, although the quantity is quite different. Limited data on discharge and sediment concentration reduces the accuracy of calculating estimates of sediment transport and sedimentation that occurs. Apart from that, the flocculation phenomenon which may occur in the Juana River which is still influenced by sea tides is also not taken into account by the HEC-RAS software in the simulation. Solution of the sedimentation problem of the Juana River can be carried out using a macro approach, namely regular dredging of the main river or with a micro approach, namely building sediment control structures in tributaries so that sediment dredging can be carried out in tributary sections that are dimensionally easier to reach than the main river.